TOTAL PROTEIN LEVEL OF BALI CATTLE POST TRANSPORTATION IN SLAUGHTERHOUSES PESANGGARAN DENPASAR - Putra, Gusti Agung Rama Wiratama; Utama, Iwan Harjono; Merdana, I MAde (Buletin Veteriner Udayana, 2022)
This study aims to determine the effect of transportation on changes in total protein levels in Bali cattle after a trip to the Pesanggaran Slaughterhouse (RPH) Denpasar. Transportation can lead to stress and dehydration. To diagnose the occurrence of stress can be done by biochemical tests. The biochemical test carried out in this study was to measure the levels of total protein in the blood. The object used is Bali cattle that have not been rested after transportation as many as 20 heads at the Denpasar Pesanggaran Slaughterhouse. Blood was taken through the auricular vein and put into a vacutainer tube containing a gel separator to separate serum from blood. Blood serum samples were taken to the Bali Provincial Health Laboratory for immediate examination of total protein levels using the Photometer 5010V5+ machine. The total protein content of the examined samples had the lowest level of 5.8 g/dL and the highest 8.5 g/dL with an average of 7.5 g/dL. From the results of the study, the total protein content of Bali cattle after transportation was considered normal, this indicated that there was no effect of transportation on the total protein content.